Determinants of Contraceptive Use at The First Sexual Intercourse among Unmarried Adolescents in Indonesia: 2017 IDHS Analysis - Sugiarti, Restya Sri; Helda, Helda; Hikmah, Kholisotul (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2022)
Adolescents confront boundaries in obtaining contraception counting prohibitive policies and adolescents possess failure to obtain contraceptives since of information, transportation, and monetary limitations. The objective of this study is to assign the variables which impact on the use of contraception for the first sexual intercourse among unmarried adolescents. Quantitative research employing cross sectional analysis was implemented in this study, by processing 2017 Indonesian Health Demographic Survey (IDHS) data. Cox regression was utilized to examine the association between sociodemographic, peer and social influences, contraceptive knowledge and contraceptive use. The study populace encompassed 705 single young people; 15 to 24 years old. The study resulted that contraceptive use at the primary sexual intercourse by single young people in Indonesia was approximately 50.35%. After bivariate analysis was applied, it was revealed that there is a significant relationship between education with the contraceptive use at the first sexual intercourse among unmarried adolescents in Indonesia (p-value = 0.049). In the final model, we discovered that the level of education and contraceptive use was statistically significant, and the contraceptive use was higher in adolescents with high education than adolescents with middle and primary education (PR 1.51, 95% CI 1.09 – 2.07, p = 0.012). Therefore, this finding provides information that education is a prominent variable for understanding contraceptive use in adolescents.